ANALISIS KELAYAKAN MODEL NAM (NEDBOR AFSTROMNINGS MODEL) UNTUK PREDIKSI KETERSEDIAAN AIR PADA DAS HO - -, Sumiati; Tika, Wayan (Agrotekno; Vol. 11, No. 2 Januari 2005, 2012)
This sudy was conducted at Ho Watershed which is located in Tabanan,Bali. The optimal parameter of the NAM model were CQOF = 0.27, Umax = 70,CLOF = 0.71, CLG = 0.45, CQIF = 0.001, CKBFU = 0.04, CLIF = 0.01, CKBFL =15, CK1 = 0.75, CBFL = 0.25, CK2= 0.50, L/Lmax = 0.8, and the initial value wereQIF2 + QOF2 = 3, U = 50, BFL = 0.001, BFU = 3.75, SM = 100.Verification of the model indicated that the NAM model was statisticallysuitable to be applied at Ho Watershed for prediction of water availability.
Keywords: Ketersediaan air, DAS, model NAM, analisis kelayakan, prediksi